Remaining Need for In Vitro Test to Elucidate 5-Hydroxytryptamine 2C Receptor Functioning. Issue 4 (August 2018) - Ivanova, Svetlana A.; Dröge, Melloney J.; Volders, Haukeline H.; van Vliet, Bernard J.; Bokhan, Nikolay A.; Bosker, Fokko J.; Loonen, Anton J.M.
Abstract : Supplemental digital content is available in the text.